Preparation and characterization of amorphous ezetimibe nanosuspensions intended for enhancement of oral bioavailability - Thadkala, Kiran; Nanam, Prema Kumari; Rambabu, Bathini; Sailu, Chinta; Aukunuru, Jithan (International Journal of Pharmaceutical Investigation)
Objectives: The objective of this study was to prepare and investigate better and stable amorphous ezetimibe nanosuspensions for oral bioavailability enhancement. Materials and Methods: Nanosuspensions of ezetimibe were prepared by solvent-antisolvent precipitation technique using the surfactant, Tween 80 as stabilizer. The nanosuspension preparation was optimized for particle size by investigating two factors that is, solvent:antisolvent ratio and surfactant concentration, at three levels. The formulations were characterized for particle size, surface morphology, crystallinity, zeta potential, saturation solubility, in vitro drug release and in vivo drug absorption. Results: The nanosuspensions of ezetimibe were successfully prepared using solvent-antisolvent precipitation. The two factors solvent:antisolvent ratio and surfactant concentration infl uenced the particle size of the nanosuspensions prepared. Nanosuspensions were smooth and spherical. The X-ray powdered diffraction and differential scanning calorimetry results indicated that the antisolventsolvent method led to the amorphization of ezetimibe. Under storage, the amorphous ezetimibe nanosuspensions demonstrated signifi cant physical stability. Ezetimibe nanosuspensions increased the saturation solubility to an extent of 4-times. Ezetimibe nanosuspensions completely dissolved in the dissolution medium within 1 h, while pure drug was dissolved up to 42% during same time. The Cmax with ezetimibe nanosuspension was approximately 3-fold higher when compared with that of ezetimibe conventional suspensions administered orally. Conclusions: Stable amorphous ezetimibe nanosuspensions were successfully prepared and these nanosuspensions demonstrated dramatic improvement in oral bioavailability of the active.
Keywords: Dissolution rate; ezetimibe; nanosuspension; oral bioavailability; solvent-antisolvent precipitation